Proceedings of the international conference on language and religion : quo vadis language and literature in the religious life? - Proceedings... (English Departement Faculty of Adab and Cultural Sciences UIN Sunan Kalijaga, 2014)
wt,1/ws.c.1/irh,c.2-3